Implementation of the Border Gateway Protocol (BGP) Protocol in the Public Network of the Universitas Muhammadiyah Semarang - Fathurohman, Akhmad; Safuan, Safuan (Journal of Intelligent Computing & Health Informatics, 2021)
The need for the smoothness and reliability of the internet network on campus is very high, especially in the current state of the need for a very high internet connection, all activities, both administrative and learning activities, are carried out online. At locations throughout the campus area, adequate availability of computer and internet network access is required. Universitas Muhammadyah Semarang (Unimus) campus which is spread across various collations of the city of Semarang, and in an integrated campus also consists of various buildings that are relatively far apart needed, therefore a network model is needed that meets all Unimus needs. Dynamic routing, also called adaptive routing, is a process where a router can forward data via a different route or given destination based on the current conditions of the communication circuits within a system. The BGP (Border Gateway Protocol) routing method which allows to provide smooth access with equal opportunities at every main network access point. This model is the choice that is applied to the Unimus public network.